Knee Position during Surgical Wound Closure in Total Knee Arthroplasty: A Review - Faour, Mhamad; Sodhi, Nipun; Khlopas, Anton; Piuzzi, Nicolas S.; Stearns, Kim L.; Krebs, Viktor E.; Higuera, Carlos A.; Mont, Michael A. (The Journal of Knee Surgery, 2018)
Study areas concerning maximizing knee range of motion (ROM) following total knee arthroplasty (TKA) have come under focus by surgeons. Among the perioperative factors that were identified to affect ROM after TKAs is knee position during surgical wound closure. Therefore, the aim of this study was to review the impact of knee position during TKA wound closure on: (1) postoperative ROM, (2) wound-related complications, (3) Knee Society Score (KSS), (4) postoperative pain, and (5) muscle strength and home functional recovery. A literature search was performed using PubMed, Ovid, and Google Scholar using various combinations of the following search terms: “wound closure,” “knee position,” “surgical closure,” and “knee arthroplasty.” The studies were evaluated for outcomes after TKA and stratified based on the knee position at surgical closure. After application of inclusion and exclusion criteria, seven studies were analyzed. The total number of patients included was 516 patients (259 patients in the flexion group and 257 patients in the full extension group). Based on the reviewed literature, wound closure in flexion was associated with significant improvement in ROM recovery at earlier follow-ups after TKA (four positive and three neutral studies), better early postoperative pain scores (two positive and one neutral study), and faster physical recovery (two positive studies) (better muscle strength and early achievement of physical therapy milestones) compared with wound closure in extension. No difference was found between wound closure in flexion compared with closure in extension in terms of long-term ROM recovery, long-term postoperative pain scores, wound-related complications (seven neutral studies), knee function measured by KSS (five neutral studies), or patient satisfactions after TKA. Although the current review is limited by the number of studies that are available in the literature, it demonstrates that overall, compared with extension, surgical wound closure in flexion may provide better ROM, faster recovery, comparable patient satisfaction, and no risk of higher wound complications.
Keywords: total knee arthroplasty; wound closure; knee position